Isolation, identification and biological features of microflora causing putridity of mustard tuber - WU Dan; CHEN Jian-chu; YE Xing-qian; JIANG Gao-qiang (浙江大学学报. 农业与生命科学版)
Seven bacteria and four microzyme were isolated from mustard tuber (Brassica juncea var. tsatsai) of package expansion. By counterevidence experiments and morphology observation and physiological experiments, two bacteria causing putridity of packaged mustard tuber were identified as Bacillus firmus and Bacillus cereus. According to the principle of turbidimetric method, using the absorbency value of bacteria culturing in liquid medium as the standard of bacteria growth, growing curve, heat-resistance and nitrate-resistance of B. firmus and B. cereus were studied. Results show that the growing-speed of B. cereus was quicker than B. firmus, but the logarithmic phase was more or less between them; low-temperature (<10 ℃) and high-salt (> 12%) could restrain growth of the two spoilage microbes effectively; and the nitrite (0%-0.15%) had no significant effect on the two spoilage microbes.